From critical appraisal to risk of bias assessment: clarifying the terminology for study evaluation in JBI systematic reviews - Stone, Jennifer C; Barker, Timothy Hugh; Aromataris, Edoardo; Ritskes-Hoitinga, Merel; Sears, Kim; Klugar, Miloslav; Leonardi-Bee, Jo; Munn, Zachary (JBI evidence synthesis, 2023)
The foundations for critical appraisal of literature have largely progressed through the development of epidemiologic research methods and the use of research to inform medical teaching and practice. This practical application of research is referred to as evidence-based medicine and has delivered a standard for the health care profession where clinicians are equally as engaged in conducting scientific research as they are in the practice of delivering treatments. Evidence-based medicine, now referred to as evidence-based health care, has generally been operationalized through empirically supported treatments, whereby the choice of treatments is substantiated by scientific support, usually by means of an evidence synthesis. As evidence synthesis methodology has advanced, guidance for the critical appraisal of primary research has emphasized a distinction from the assessment of internal validity required for synthesized research. This assessment is conceptualized and branded in various ways in the literature, such as risk of bias, critical appraisal, study validity, methodological quality, and methodological limitations. This paper provides a discussion of the definitions and characteristics of these terms, concluding with a recommendation for JBI to adopt the term "risk of bias" assessment.
Keywords: výzkumný projekt; Research Design; Bias; lidé; zkreslení výsledků (epidemiologie); Humans